Method for producing dip-molded body

JP7635777B2Active Publication Date: 2025-02-26ZEON CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022503234
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-27
Filing Date
2021-02-08
Publication Date
2025-02-26
Estimated Expiration
2041-02-08

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、引張強度、引張伸び、および引裂強度に優れ、ピンホールなどの構造欠陥の発生が抑制されたディップ成形体を製造するための方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635777000001
    Figure 0007635777000001
  • Figure 0007635777000002
    Figure 0007635777000002
Patent Text Reader

Abstract

Provided is a method for producing a dip-molded article, the method comprising the steps of: immersing a dip molding die in a coagulant agent solution to cause a coagulant agent to be adhered onto the dip molding die; preparing a latex composition which contains a carboxy-modified conjugated diene-based polymer latex in which carboxy-modified conjugated diene-based polymer particles having a volume average particle diameter of 500 to 2,000 nm are dispersed in water; and immersing the dip molding die having the coagulant agent adhered thereon in the latex composition to produce a dip-molded article having a thickness of 0.02 to 0.19 mm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a dip-formed article which is excellent in tensile strength, tensile elongation and tear strength and in which the occurrence of structural defects such as pinholes is suppressed. [Background technology]

[0002] It has been known that latex compositions containing natural rubber latex are dip molded to obtain film-formed articles such as dip molded articles that are used in contact with the human body, such as nipples, balloons, gloves, balloons, and sacks. However, natural rubber latex contains proteins that cause symptoms of immediate-type allergy (Type I) in the human body, and therefore may be problematic as a dip molded article that comes into direct contact with the mucous membranes or organs of the body. For this reason, studies have been made on removing proteins in natural rubber latex by purification or the like, or on using synthetic rubber latex instead of natural rubber.

[0003] For example, Patent Document 1 discloses a latex composition for dip molding, which is obtained by compounding zinc oxide, sulfur, and a vulcanization accelerator with a latex of synthetic polyisoprene, which is a synthetic rubber. However, when a relatively thin dip-molded body is produced by the technique of Patent Document 1, structural defects such as pinholes are likely to occur, and the tensile strength, tensile elongation, and tear strength of the obtained dip-molded body are not sufficient. Therefore, it has been desired to improve the tensile strength, tensile elongation, and tear strength of the dip-molded body and to suppress the occurrence of structural defects when a relatively thin dip-molded body is produced. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2014 / 129547 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a method for producing a dip-molded body that has excellent tensile strength, tensile elongation, and tear strength and is suppressed in the occurrence of structural defects such as pinholes. [Means for solving the problem]

[0006] As a result of intensive research into achieving the above object, the present inventors have found that the above object can be achieved by using a latex composition containing a latex of a carboxy-modified conjugated diene-based polymer having a specific particle size and by making the obtained dip-molded body have a thickness in a specific range, and have thus completed the present invention.

[0007] That is, according to the present invention, there is provided a method for producing a dip-molded body, comprising the steps of: immersing a dip-molding mold in a coagulant solution to adhere a coagulant to the dip-molding mold; preparing a latex composition containing a carboxy-modified conjugated diene-based polymer latex in which particles of a carboxy-modified conjugated diene-based polymer having a volume average particle size of 500 to 2,000 nm are dispersed in water; and immersing the dip-molding mold to which the coagulant has been adhered in the latex composition to obtain a dip-molded body having a thickness of 0.02 to 0.19 mm.

[0008] In the method for producing a dip-formed article of the present invention, the thickness of the dip-formed article is preferably 0.02 to 0.15 mm, more preferably 0.02 to 0.10 mm, and even more preferably 0.02 mm or more and less than 0.08 mm. In the method for producing a dip-molded article of the present invention, it is preferable to use a dip-molding mold whose surface has not been roughened. In the method for producing a dip-formed article of the present invention, the coagulant solution preferably has a coagulant concentration of 0.1 to 20% by weight. In the method for producing a dip-formed article of the present invention, the immersion time when the dip-forming mold is immersed in the coagulant solution is preferably 0.1 to 20 seconds. In the method for producing a dip-formed article of the present invention, the temperature of the dip-forming mold is preferably set to 20 to 100°C when the dip-forming mold is immersed in the coagulant solution. In the method for producing a dip-molded article of the present invention, the immersion time when the dip-molding mold to which the coagulant is attached is immersed in the latex composition is preferably 1 to 20 seconds. In the method for producing a dip-molded article of the present invention, the solid content of the latex composition is preferably 1 to 40% by weight. In the method for producing a dip-molded article of the present invention, the carboxy-modified conjugated diene polymer latex is preferably synthetic polyisoprene, a styrene-isoprene-styrene block copolymer, or a deproteinized natural rubber latex. In the method for producing a dip-molded article of the present invention, it is preferable that the latex composition further contains a sulfur-based vulcanizing agent. In the method for producing a dip-molded article of the present invention, it is preferable that the latex composition further contains a vulcanization accelerator. In the method for producing a dip-molded article of the present invention, the vulcanization accelerator is preferably a xanthogen compound. Effect of the Invention

[0009] According to the present invention, it is possible to provide a method for producing a dip-formed article which is excellent in tensile strength, tensile elongation and tear strength and in which the occurrence of structural defects such as pinholes is suppressed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The method for producing the dip-molded article of the present invention includes the steps of: A step of immersing a dip-forming mold in a coagulant solution to adhere the coagulant to the dip-forming mold; A step of preparing a latex composition containing a carboxy-modified conjugated diene polymer latex in which particles of a carboxy-modified conjugated diene polymer having a volume average particle diameter of 500 to 2,000 nm are dispersed in water; and immersing the dip-molding mold to which the coagulant has been attached in the latex composition to obtain a dip-molded product having a thickness of 0.02 to 0.19 mm.

[0011] <Latex composition> The latex composition used in the present invention contains a carboxy-modified conjugated diene polymer latex. The carboxy-modified conjugated diene polymer latex is a carboxy-modified conjugated diene polymer latex obtained by modifying a conjugated diene polymer with a monomer having a carboxyl group.

[0012] The conjugated diene polymer is not particularly limited, but examples thereof include synthetic polyisoprene, styrene-isoprene-styrene block copolymer (SIS), natural rubber from which proteins have been removed (deproteinized natural rubber), nitrile group-containing conjugated diene copolymer, etc. Among these, polymers containing isoprene units such as synthetic polyisoprene, SIS, and deproteinized natural rubber are preferred, and synthetic polyisoprene is particularly preferred.

[0013] When synthetic polyisoprene is used as the conjugated diene polymer, the synthetic polyisoprene may be a homopolymer of isoprene or a copolymer of isoprene and another ethylenically unsaturated monomer that is copolymerizable with isoprene. The content of isoprene units in the synthetic polyisoprene is preferably 70% by weight or more, more preferably 90% by weight or more, even more preferably 95% by weight or more, and particularly preferably 100% by weight (homopolymer of isoprene) based on the total monomer units, since it is easy to obtain a dip-molded product that is flexible and has excellent tensile strength.

[0014] Examples of other ethylenically unsaturated monomers copolymerizable with isoprene include conjugated diene monomers other than isoprene, such as butadiene, chloroprene, and 1,3-pentadiene; ethylenically unsaturated nitrile monomers, such as acrylonitrile, methacrylonitrile, fumaronitrile, and α-chloroacrylonitrile; vinyl aromatic monomers, such as styrene and alkylstyrene; ethylenically unsaturated carboxylate monomers, such as methyl (meth)acrylate (meaning "methyl acrylate and / or methyl methacrylate", hereinafter the same applies to ethyl (meth)acrylate, etc.), ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; and the like. These other ethylenically unsaturated monomers copolymerizable with isoprene may be used alone or in combination.

[0015] Synthetic polyisoprene can be obtained by a conventional method, for example, by solution polymerization of isoprene and other copolymerizable ethylenically unsaturated monomers, which are used as necessary, in an inert polymerization solvent using a Ziegler-based polymerization catalyst consisting of trialkylaluminum-titanium tetrachloride or an alkyl lithium polymerization catalyst such as n-butyl lithium or sec-butyl lithium. The polymer solution of synthetic polyisoprene obtained by solution polymerization may be used as it is for the production of synthetic polyisoprene latex, but after removing solid synthetic polyisoprene from the polymer solution, it can also be dissolved in an organic solvent and used for the production of synthetic polyisoprene latex. The synthetic polyisoprene latex can be used for the production of a latex of a carboxy-modified conjugated diene polymer used in the present invention, as described later. When the synthetic polyisoprene polymer solution is obtained by the above-mentioned method, impurities such as the residue of the polymerization catalyst remaining in the polymer solution may be removed. In addition, an antioxidant described later may be added to the solution during or after the polymerization. In addition, commercially available solid synthetic polyisoprene may be used.

[0016] There are four types of isoprene units in synthetic polyisoprene, depending on the bonding state of isoprene: cis bond unit, trans bond unit, 1,2-vinyl bond unit, and 3,4-vinyl bond unit. From the viewpoint of improving the tensile strength of the obtained dip-molded article, the content of cis bond units in the isoprene units contained in the synthetic polyisoprene is preferably 70% by weight or more, more preferably 90% by weight or more, and even more preferably 95% by weight or more, based on the total isoprene units.

[0017] The weight-average molecular weight of the synthetic polyisoprene is preferably 10,000 to 5,000,000, more preferably 500,000 to 5,000,000, and even more preferably 800,000 to 3,000,000, as calculated using standard polystyrene standards by gel permeation chromatography analysis. By setting the weight-average molecular weight of the synthetic polyisoprene within the above range, the tensile strength, tensile elongation, and tear strength of the dip-molded article are improved, and the synthetic polyisoprene latex tends to be easily produced.

[0018] In addition, the polymer Mooney viscosity (ML 1+4 , 100° C.) is preferably 50 to 80, more preferably 60 to 80, and further preferably 70 to 80.

[0019] Examples of methods for obtaining synthetic polyisoprene latex include (1) a method in which a solution or fine suspension of synthetic polyisoprene dissolved or finely dispersed in an organic solvent is emulsified in water in the presence of an emulsifier, and the organic solvent is removed as necessary to produce a synthetic polyisoprene latex, and (2) a method in which isoprene alone or a mixture of isoprene and an ethylenically unsaturated monomer copolymerizable therewith is emulsion polymerized or suspension polymerized in the presence of an emulsifier to directly produce a synthetic polyisoprene latex. Among these, the above-mentioned production method (1) is preferred in that it can use synthetic polyisoprene having a high ratio of cis-bond units in the isoprene units and can easily produce a dip-molded product having excellent mechanical properties such as tensile strength.

[0020] Examples of the organic solvent used in the above production method (1) include aromatic hydrocarbon solvents such as benzene, toluene, xylene, etc.; alicyclic hydrocarbon solvents such as cyclopentane, cyclopentene, cyclohexane, cyclohexene, etc.; aliphatic hydrocarbon solvents such as pentane, hexane, heptane, etc.; halogenated hydrocarbon solvents such as methylene chloride, chloroform, ethylene dichloride, etc. Among these, alicyclic hydrocarbon solvents and aliphatic hydrocarbon solvents are preferred, pentane, cyclohexane, and n-hexane are more preferred, and n-hexane is particularly preferred.

[0021] The amount of the organic solvent used is preferably 2,000 parts by weight or less, more preferably 20 to 1,500 parts by weight, and even more preferably 500 to 1,500 parts by weight, based on 100 parts by weight of the synthetic polyisoprene.

[0022] As the emulsifier used in the above production method (1), it is preferable to use an ionic emulsifier, and among them, it is more preferable to use an anionic emulsifier. Examples of the anionic emulsifier include fatty acid salts such as sodium laurate, potassium myristate, sodium palmitate, potassium oleate, sodium linolenate, sodium rosinate, and potassium rosinate; alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate, potassium dodecylbenzenesulfonate, sodium decylbenzenesulfonate, potassium decylbenzenesulfonate, sodium cetylbenzenesulfonate, and potassium cetylbenzenesulfonate; alkylsulfosuccinates such as sodium di(2-ethylhexyl)sulfosuccinate, potassium di(2-ethylhexyl)sulfosuccinate, and sodium dioctylsulfosuccinate; alkyl sulfates such as sodium lauryl sulfate and potassium lauryl sulfate; polyoxyethylene alkyl ether sulfates such as sodium polyoxyethylene lauryl ether sulfate and potassium polyoxyethylene lauryl ether sulfate; and monoalkyl phosphates such as sodium lauryl phosphate and potassium lauryl phosphate.

[0023] Among these anionic emulsifiers, fatty acid salts, alkylbenzenesulfonates, alkylsulfosuccinates, alkyl sulfates and polyoxyethylene alkyl ether sulfates are preferred, with fatty acid salts and alkylbenzenesulfonates being particularly preferred.

[0024] In addition, it is preferable to use at least one selected from the group consisting of alkylbenzenesulfonate, alkylsulfosuccinate, alkylsulfuric acid ester salt, and polyoxyethylene alkyl ether sulfate salt in combination with a fatty acid salt, since it is possible to more efficiently remove a trace amount of polymerization catalyst (particularly aluminum and titanium) derived from synthetic polyisoprene and suppress the generation of coagulation during the production of a latex composition, and it is particularly preferable to use an alkylbenzenesulfonate in combination with a fatty acid salt. Here, as the fatty acid salt, sodium rosinate and potassium rosinate are preferable, and as the alkylbenzenesulfonate, sodium dodecylbenzenesulfonate and potassium dodecylbenzenesulfonate are preferable. In addition, these emulsifiers may be used alone or in combination of two or more.

[0025] As described above, by using at least one selected from the group consisting of alkylbenzenesulfonates, alkyl sulfosuccinates, alkyl sulfates, and polyoxyethylene alkyl ether sulfates in combination with a fatty acid salt, the obtained latex contains at least one selected from the group consisting of alkylbenzenesulfonates, alkyl sulfosuccinates, alkyl sulfates, and polyoxyethylene alkyl ether sulfates, and a fatty acid salt.

[0026] Examples of ionic emulsifiers other than anionic emulsifiers include copolymerizable emulsifiers such as sulfoesters of α,β-unsaturated carboxylic acids, sulfate esters of α,β-unsaturated carboxylic acids, and sulfoalkylaryl ethers.

[0027] Furthermore, nonionic emulsifiers such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, and polyoxyethylene sorbitan alkyl esters may also be used in combination, so long as they do not inhibit coagulation by the coagulant used in dip molding.

[0028] The amount of the emulsifier used in the above production method (1) is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, based on 100 parts by weight of synthetic polyisoprene. When two or more kinds of emulsifiers are used, it is preferable that the total amount of these is within the above range. That is, for example, when at least one selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate ester salt, and polyoxyethylene alkyl ether sulfate ester salt is used in combination with a fatty acid salt, it is preferable that the total amount of these is within the above range. By setting the amount of the emulsifier to the above range, the generation of aggregates during emulsification can be further suppressed.

[0029] In addition, when at least one selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate, and polyoxyethylene alkyl ether sulfate is used in combination with a fatty acid salt as an anionic emulsifier, the weight ratio of the "fatty acid salt" to the "total of at least one emulsifier selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate, and polyoxyethylene alkyl ether sulfate" is preferably in the range of 1:1 to 10:1, more preferably in the range of 1:1 to 7:1. By setting the weight ratio of at least one emulsifier selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate, and polyoxyethylene alkyl ether sulfate in the above range, foaming that occurs when handling synthetic polyisoprene can be suppressed, which eliminates the need for operations such as leaving the mixture for a long time or adding an antifoaming agent, leading to improved workability and reduced costs.

[0030] The amount of water used in the above production method (1) is preferably 10 to 1,000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight, relative to 100 parts by weight of the organic solvent solution of synthetic polyisoprene. The type of water used may be hard water, soft water, ion-exchanged water, distilled water, zeolite water, etc., with soft water, ion-exchanged water, and distilled water being preferred.

[0031] The device for emulsifying the solution or fine suspension of synthetic polyisoprene dissolved or finely dispersed in an organic solvent in water in the presence of an emulsifier is not particularly limited, and can be any device that is commercially available as an emulsifier or disperser. The method for adding the emulsifier to the solution or fine suspension of synthetic polyisoprene is not particularly limited, and the emulsifier may be added in advance to either water or the solution or fine suspension of synthetic polyisoprene, or to both, or may be added to the emulsion during the emulsification operation, or may be added all at once or in portions.

[0032] Examples of emulsifying devices include batch emulsifying machines such as "Homogenizer" (manufactured by IKA), "Polytron" (manufactured by Kinematica), and "TK Auto Homo Mixer" (manufactured by Tokushu Kika Kogyo); "TK Pipeline Homo Mixer" (manufactured by Tokushu Kika Kogyo), "Colloid Mill" (manufactured by Kobe Steel Pantech), "Thrasher" (manufactured by Nippon Coke & Engineering Co., Ltd.), "Trigonal Wet Fine Grinding Mill" (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), "Cavitron" (manufactured by Eurotech), and Examples of such machines include continuous emulsifiers such as "Milder" (manufactured by Pacific Machinery & Engineering Co., Ltd.) and "Fine Flow Mill" (manufactured by Pacific Machinery & Engineering Co., Ltd.); high-pressure emulsifiers such as "Microfluidizer" (manufactured by Mizuho Kogyo Co., Ltd.), "Nanomizer" (manufactured by Nanomizer Co., Ltd.), and "APV Gaulin" (manufactured by Gaulin Co., Ltd.); membrane emulsifiers such as "Membrane Emulsifier" (manufactured by Reika Kogyo Co., Ltd.); vibration emulsifiers such as "Vibro Mixer" (manufactured by Reika Kogyo Co., Ltd.); and ultrasonic emulsifiers such as "Ultrasonic Homogenizer" (manufactured by Branson Co., Ltd.). The conditions for the emulsification operation using an emulsification device are not particularly limited, and the processing temperature, processing time, and the like may be appropriately selected so as to achieve the desired dispersion state.

[0033] In the above production method (1), it is desirable to remove the organic solvent from the emulsion obtained through the emulsification operation. As a method for removing the organic solvent from the emulsion, a method capable of reducing the content of the organic solvent (preferably an alicyclic hydrocarbon solvent or an aliphatic hydrocarbon solvent) in the obtained synthetic polyisoprene latex to 500 ppm by weight or less is preferable, and for example, a method such as reduced pressure distillation, normal pressure distillation, steam distillation, and centrifugation can be adopted. The organic solvent can be removed while adding the defoaming agent, which can suppress foaming of the synthetic polyisoprene.

[0034] Furthermore, after removing the organic solvent, in order to increase the solid content concentration of the synthetic polyisoprene latex, a concentration operation may be carried out by a method such as reduced pressure distillation, normal pressure distillation, centrifugation, membrane concentration, etc., as necessary. In particular, from the viewpoint of increasing the solid content concentration of the synthetic polyisoprene latex and reducing the residual amount of the emulsifier in the synthetic polyisoprene latex, it is preferable to carry out centrifugation.

[0035] The centrifugation is preferably carried out using a continuous centrifuge under the conditions of a centrifugal force of preferably 100 to 10,000 G, a solids concentration of the synthetic polyisoprene latex before centrifugation of preferably 2 to 15% by weight, a flow rate of the centrifuge of preferably 500 to 1700 kg / hr, and a back pressure (gauge pressure) of the centrifuge of preferably 0.03 to 1.6 MPa, and a synthetic polyisoprene latex can be obtained as a light liquid after centrifugation. This can reduce the amount of emulsifier remaining in the synthetic polyisoprene latex.

[0036] The solid content of the synthetic polyisoprene latex is preferably 30 to 70% by weight, more preferably 40 to 70% by weight, and further preferably 50 to 70% by weight. By making the solid content at or above the lower limit of the above range, the dip-molded article described below is less likely to break. In addition, by making the solid content at or below the upper limit of the above range, the viscosity of the synthetic polyisoprene latex is prevented from becoming too high, and it becomes easy to transport it through piping or to stir it in a mixing tank.

[0037] The volume average particle diameter of the synthetic polyisoprene latex is preferably 0.1 to 10 μm, more preferably 0.5 to 3 μm, and further preferably 0.5 to 2.0 μm. By setting the volume average particle diameter within the above range, the latex viscosity becomes appropriate and easy to handle, and also the formation of a film on the surface of the latex during storage of the synthetic polyisoprene latex can be suppressed.

[0038] The synthetic polyisoprene latex may further contain additives that are commonly used in the field of latex, such as a pH adjuster, an antifoaming agent, a preservative, a crosslinking agent, a chelating agent, an oxygen scavenger, a dispersant, and an antioxidant.

[0039] Examples of pH adjusters include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal bicarbonates such as sodium bicarbonate; ammonia; and organic amine compounds such as trimethylamine and triethanolamine; with alkali metal hydroxides or ammonia being preferred.

[0040] As described above, the conjugated diene polymer may be a styrene-isoprene-styrene block copolymer (SIS), where "S" represents a styrene block and "I" represents an isoprene block.

[0041] SIS can be obtained by a conventional method, for example, block copolymerization of isoprene and styrene in an inert polymerization solvent using an active organic metal such as n-butyl lithium as an initiator. The obtained SIS polymer solution may be used as is for the production of SIS latex, but after removing solid SIS from the polymer solution, the solid SIS can be dissolved in an organic solvent and used for the production of SIS latex. As described later, SIS latex can be used for the production of the latex of the carboxy-modified polymer used in the present invention. The method for producing SIS latex is not particularly limited, but a method in which a solution or fine suspension of SIS dissolved or finely dispersed in an organic solvent is emulsified in water in the presence of an emulsifier, and the organic solvent is removed as necessary to produce SIS latex is preferred. In this case, impurities such as the residue of the polymerization catalyst remaining in the polymer solution after synthesis may be removed. In addition, an antioxidant, which will be described later, may be added to the solution during or after polymerization. Commercially available solid SIS may also be used.

[0042] As the organic solvent, the same ones as in the case of the synthetic polyisoprene can be used, and aromatic hydrocarbon solvents and alicyclic hydrocarbon solvents are preferred, with cyclohexane and toluene being particularly preferred. The amount of the organic solvent used is usually 50 to 2,000 parts by weight, preferably 80 to 1,000 parts by weight, more preferably 100 to 500 parts by weight, and further preferably 150 to 300 parts by weight, based on 100 parts by weight of the SIS.

[0043] Examples of the emulsifier include the same ones as those in the case of the synthetic polyisoprene, and anionic emulsifiers are preferred, with potassium rosinate and sodium dodecylbenzenesulfonate being particularly preferred.

[0044] The amount of the emulsifier used is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, based on 100 parts by weight of the SIS. By setting the amount of the emulsifier used within the above range, the stability of the obtained latex can be improved.

[0045] The amount of water used in the above-mentioned SIS latex production method is preferably 10 to 1,000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight, based on 100 parts by weight of the SIS organic solvent solution. The type of water used may include hard water, soft water, ion-exchanged water, distilled water, zeolite water, etc. Also, a polar solvent, typified by an alcohol such as methanol, may be used in combination with water.

[0046] The apparatus for emulsifying the organic solvent solution or fine suspension of SIS in water in the presence of an emulsifier can be the same as that for the synthetic polyisoprene. The method of adding the emulsifier is not particularly limited, and it may be added in advance to either the water or the organic solvent solution or fine suspension of SIS, or to both, or it may be added to the emulsion during the emulsification operation, or it may be added all at once or in portions.

[0047] In the above-mentioned method for producing SIS latex, it is preferable to obtain SIS latex by removing the organic solvent from the emulsion obtained through the emulsification operation. The method for removing the organic solvent from the emulsion is not particularly limited, and methods such as reduced pressure distillation, normal pressure distillation, steam distillation, and centrifugation can be adopted. The organic solvent can be removed while adding the defoaming agent. The addition of the defoaming agent can suppress foaming.

[0048] After removing the organic solvent, the SIS latex may be concentrated by vacuum distillation, atmospheric distillation, centrifugation, membrane concentration or the like, if necessary, in order to increase the solids concentration of the SIS latex.

[0049] The solid content of the SIS latex is preferably 30 to 70% by weight, more preferably 40 to 70% by weight, and further preferably 50 to 70% by weight. By making the solid content equal to or higher than the lower limit of the above range, the dip-molded product described below is less likely to break. Furthermore, by making the solid content equal to or lower than the upper limit of the above range, the viscosity of the SIS latex is prevented from becoming too high, and it becomes easy to transport it through piping or to stir it in a mixing tank.

[0050] In addition, SIS latex may contain additives such as pH adjusters, antifoamers, preservatives, crosslinking agents, chelating agents, oxygen scavengers, dispersants, and antioxidants, which are generally used in the field of latex. Examples of pH adjusters include the same ones as those in the case of synthetic polyisoprene, and alkali metal hydroxides or ammonia are preferred. The pH of the SIS latex is not particularly limited, but as described below, when a latex composition is made using SIS latex or the like and the latex composition is aged under a specified condition, it is preferred that the pH of the latex composition before aging is 10 or more.

[0051] The content of styrene units in the styrene block in the SIS contained in the SIS latex thus obtained is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and further preferably 100% by weight, based on the total monomer units. The content of isoprene units in the isoprene block in the SIS is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and further preferably 100% by weight, based on the total monomer units. The content ratio of styrene units and isoprene units in SIS, in terms of the weight ratio of "styrene units:isoprene units", is usually in the range of 1:99 to 90:10, preferably 3:97 to 70:30, more preferably 5:95 to 50:50, and further preferably 10:90 to 30:70.

[0052] The weight-average molecular weight of the SIS, calculated as standard polystyrene by gel permeation chromatography analysis, is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and further preferably 100,000 to 300,000. By setting the weight-average molecular weight of the SIS within the above range, the balance between the tensile strength and flexibility of the dip-molded article is improved, and the production of the SIS latex tends to be facilitated.

[0053] The volume average particle diameter of the latex particles (SIS particles) in the SIS latex is preferably 0.1 to 10 μm, more preferably 0.5 to 3 μm, and further preferably 0.5 to 2.0 μm. By setting the volume average particle diameter of the latex particles within the above range, the viscosity of the latex becomes appropriate, making it easy to handle, and also preventing a film from being formed on the surface of the latex during storage of the SIS latex.

[0054] As the conjugated diene polymer, a nitrile group-containing conjugated diene copolymer can also be used, as described above.

[0055] The nitrile group-containing conjugated diene copolymer is a copolymer obtained by copolymerizing a conjugated diene monomer with an ethylenically unsaturated nitrile monomer, and may also be a copolymer obtained by copolymerizing, in addition to the above, other ethylenically unsaturated monomers copolymerizable therewith, which are used as necessary.

[0056] Examples of the conjugated diene monomer include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, and chloroprene. Among these, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred. These conjugated diene monomers can be used alone or in combination of two or more. The content of the conjugated diene monomer unit formed by the conjugated diene monomer in the nitrile group-containing conjugated diene copolymer is preferably 56 to 78% by weight, more preferably 56 to 73% by weight, and even more preferably 56 to 68% by weight. By setting the content of the conjugated diene monomer unit within the above range, the obtained dip-molded article can be made to have sufficient tensile strength while being excellent in texture and elongation.

[0057] The ethylenically unsaturated nitrile monomer is not particularly limited as long as it is an ethylenically unsaturated monomer containing a nitrile group, and examples thereof include acrylonitrile, methacrylonitrile, fumaronitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, etc. Among them, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred. These ethylenically unsaturated nitrile monomers can be used alone or in combination of two or more. The content ratio of the ethylenically unsaturated nitrile monomer unit formed by the ethylenically unsaturated nitrile monomer in the nitrile group-containing conjugated diene copolymer is preferably 20 to 40% by weight, more preferably 25 to 40% by weight, and even more preferably 30 to 40% by weight. By setting the content of the ethylenically unsaturated nitrile monomer unit within the above range, the obtained dip-molded product can be made to have sufficient tensile strength while being more excellent in texture and elongation.

[0058] Examples of other ethylenically unsaturated monomers copolymerizable with the conjugated diene monomer and the ethylenically unsaturated nitrile monomer include ethylenically unsaturated carboxylic acid monomers, which are ethylenically unsaturated monomers containing a carboxyl group; vinyl aromatic monomers such as styrene, alkylstyrene, and vinylnaphthalene; fluoroalkyl vinyl ethers such as fluoroethyl vinyl ether; ethylenically unsaturated amide monomers such as (meth)acrylamide, N-methylol (meth)acrylamide, N,N-dimethylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, and N-propoxymethyl (meth)acrylamide; methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, dibutyl maleate, and fumarate. Examples of the ethylenically unsaturated carboxylic acid ester monomers include dibutyl acrylate, diethyl maleate, methoxymethyl (meth)acrylate, ethoxyethyl (meth)acrylate, methoxyethoxyethyl (meth)acrylate, cyanomethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 1-cyanopropyl (meth)acrylate, 2-ethyl-6-cyanohexyl (meth)acrylate, 3-cyanopropyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, glycidyl (meth)acrylate, and dimethylaminoethyl (meth)acrylate; and crosslinkable monomers such as divinylbenzene, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol (meth)acrylate. These ethylenically unsaturated monomers can be used alone or in combination of two or more.

[0059] The ethylenically unsaturated carboxylic acid monomer is not particularly limited as long as it is an ethylenically unsaturated monomer containing a carboxyl group, and examples thereof include ethylenically unsaturated monocarboxylic acid monomers such as acrylic acid and methacrylic acid; ethylenically unsaturated polyvalent carboxylic acid monomers such as itaconic acid, maleic acid, and fumaric acid; ethylenically unsaturated polyvalent carboxylic acid anhydrides such as maleic anhydride and citraconic anhydride; ethylenically unsaturated polyvalent carboxylic acid partial ester monomers such as monobutyl fumarate, monobutyl maleate, and mono-2-hydroxypropyl maleate; and the like. Among these, ethylenically unsaturated monocarboxylic acids are preferred, and methacrylic acid is particularly preferred. These ethylenically unsaturated carboxylic acid monomers can also be used as alkali metal salts or ammonium salts. Moreover, the ethylenically unsaturated carboxylic acid monomers can be used alone or in combination of two or more. The content of ethylenically unsaturated carboxylic acid monomer units formed by ethylenically unsaturated carboxylic acid monomers in the nitrile group-containing conjugated diene copolymer is preferably 2 to 5% by weight, more preferably 2 to 4.5% by weight, and further preferably 2.5 to 4.5% by weight. By setting the content of the ethylenically unsaturated carboxylic acid monomer units within the above range, the obtained dip-molded article can be made to have sufficient tear strength and excellent texture.

[0060] In the nitrile group-containing conjugated diene copolymer, the content of other monomer units formed by other ethylenically unsaturated monomers is preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 3% by weight or less.

[0061] The nitrile group-containing conjugated diene copolymer can be obtained by copolymerizing a monomer mixture containing the above-mentioned monomers, and a method of copolymerizing by emulsion polymerization is preferred. As the emulsion polymerization method, a conventionally known method can be adopted.

[0062] When the monomer mixture containing the above-mentioned monomers is emulsion-polymerized, it is possible to use commonly used polymerization auxiliary materials such as an emulsifier, a polymerization initiator, a molecular weight regulator, etc. The method of adding these polymerization auxiliary materials is not particularly limited, and any method such as initial lump-sum addition, divided addition, or continuous addition may be used.

[0063] The emulsifier is not particularly limited, but examples thereof include nonionic emulsifiers such as polyoxyethylene alkyl ether, polyoxyethylene alkylphenol ether, polyoxyethylene alkyl ester, and polyoxyethylene sorbitan alkyl ester; anionic emulsifiers such as alkylbenzene sulfonate salts such as potassium dodecylbenzene sulfonate and sodium dodecylbenzene sulfonate, higher alcohol sulfate salts, and alkyl sulfosuccinate salts; cationic emulsifiers such as alkyltrimethylammonium chloride, dialkylammonium chloride, and benzylammonium chloride; and copolymerizable emulsifiers such as sulfoesters of α,β-unsaturated carboxylic acids, sulfate esters of α,β-unsaturated carboxylic acids, and sulfoalkylaryl ethers. Among these, anionic emulsifiers are preferred, alkylbenzene sulfonates are more preferred, and potassium dodecylbenzene sulfonate and sodium dodecylbenzene sulfonate are particularly preferred. These emulsifiers can be used alone or in combination of two or more. The amount of emulsifier used is preferably 0.1 to 10 parts by weight based on 100 parts by weight of the monomer mixture.

[0064] The polymerization initiator is not particularly limited, but examples thereof include inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as diisopropylbenzene hydroperoxide, cumene hydroperoxide, t-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, di-t-butyl peroxide, di-α-cumyl peroxide, acetyl peroxide, isobutyryl peroxide, and benzoyl peroxide; and azo compounds such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and methyl azobisisobutyrate. These polymerization initiators can be used alone or in combination of two or more kinds. The amount of the polymerization initiator used is preferably 0.01 to 10 parts by weight, more preferably 0.01 to 2 parts by weight, based on 100 parts by weight of the monomer mixture.

[0065] The peroxide initiator can be used as a redox polymerization initiator in combination with a reducing agent. The reducing agent is not particularly limited, but includes compounds containing reduced metal ions such as ferrous sulfate and cuprous naphthenate; sulfonic acid compounds such as sodium methanesulfonate; and amine compounds such as dimethylaniline. These reducing agents can be used alone or in combination of two or more. The amount of the reducing agent used is preferably 3 to 1000 parts by weight per 100 parts by weight of the peroxide.

[0066] The amount of water used in emulsion polymerization is preferably from 80 to 600 parts by weight, particularly preferably from 100 to 200 parts by weight, based on 100 parts by weight of the total monomers used.

[0067] Examples of the method of adding the monomers include a method of adding the monomers to be used in a reaction vessel all at once, a method of adding them continuously or intermittently as the polymerization proceeds, a method of adding a part of the monomers and reacting them to a specific conversion rate, and then polymerizing by adding the remaining monomers continuously or intermittently, and any of these methods may be adopted. When the monomers are mixed and added continuously or intermittently, the composition of the mixture may be constant or may be changed. In addition, the various monomers to be used may be mixed in advance and then added to the reaction vessel, or each monomer may be added to the reaction vessel separately.

[0068] Furthermore, if necessary, polymerization auxiliary materials such as a chelating agent, a dispersing agent, a pH adjuster, an oxygen scavenger, and a particle size adjuster can be used, and the type and the amount of these are not particularly limited.

[0069] The polymerization temperature when carrying out the emulsion polymerization is not particularly limited, but is usually 3 to 95° C., and preferably 5 to 60° C. The polymerization time is about 5 to 40 hours.

[0070] As described above, the monomer mixture is emulsion-polymerized, and when a predetermined polymerization conversion rate is reached, the polymerization reaction is terminated by cooling the polymerization system or adding a polymerization terminator. The polymerization conversion rate at the time of terminating the polymerization reaction is preferably 90% by weight or more, more preferably 93% by weight or more.

[0071] The polymerization terminator is not particularly limited, but examples thereof include hydroxylamine, hydroxylamine sulfate, diethylhydroxylamine, hydroxylamine sulfonic acid and its alkali metal salts, sodium dimethyldithiocarbamate, hydroquinone derivatives, catechol derivatives, and aromatic hydroxydithiocarboxylic acids such as hydroxydimethylbenzenethiocarboxylic acid, hydroxydiethylbenzenedithiocarboxylic acid, and hydroxydibutylbenzenedithiocarboxylic acid, and their alkali metal salts. The amount of the polymerization terminator used is preferably 0.05 to 2 parts by weight based on 100 parts by weight of the monomer mixture.

[0072] After the polymerization reaction is terminated, if desired, unreacted monomers are removed and the solid content and pH are adjusted to obtain a latex of a nitrile group-containing conjugated diene copolymer.

[0073] Furthermore, to the latex of the nitrile group-containing conjugated diene copolymer, an antioxidant, a preservative, an antibacterial agent, a dispersant, etc. may be appropriately added, if necessary.

[0074] The number average particle size of the latex of the nitrile group-containing conjugated diene copolymer is preferably 60 to 300 nm, more preferably 80 to 150 nm. The particle size can be adjusted to a desired value by, for example, adjusting the amounts of the emulsifier and polymerization initiator used.

[0075] As the conjugated diene polymer, natural rubber from which proteins have been removed (deproteinized natural rubber) can also be used, as described above. The deproteinized natural rubber can be what is known as "deproteinized natural rubber" obtained by a known protein removal method, such as a method in which proteins in natural rubber are decomposed with a protease or a surfactant, and then removed by washing or centrifugation.

[0076] As described above, the conjugated diene polymer used in the present invention may be synthetic polyisoprene, styrene-isoprene-styrene block copolymer (SIS), nitrile group-containing conjugated diene copolymer, deproteinized natural rubber, or the like. However, the present invention is not limited to these, and may also use butadiene polymer, styrene-butadiene copolymer, or the like.

[0077] The butadiene polymer may be a homopolymer of 1,3-butadiene as a conjugated diene monomer, or a copolymer obtained by copolymerizing 1,3-butadiene as a conjugated diene monomer with another ethylenically unsaturated monomer that is copolymerizable with the conjugated diene monomer.

[0078] The styrene-butadiene copolymer is a copolymer obtained by copolymerizing styrene with 1,3-butadiene as a conjugated diene monomer, and may also be a copolymer obtained by copolymerizing, in addition to these, other ethylenically unsaturated monomers copolymerizable therewith, which are used as necessary.

[0079] The carboxy-modified conjugated diene polymer constituting the carboxy-modified conjugated diene polymer latex used in the present invention can be obtained by modifying the above-mentioned conjugated diene polymer with a monomer having a carboxyl group. When an ethylenically unsaturated carboxylic acid monomer is used as another copolymerizable ethylenically unsaturated monomer in producing a nitrile group-containing conjugated diene copolymer, the produced nitrile group-containing conjugated diene copolymer is already carboxy-modified, so modification with a monomer having a carboxyl group described below is not necessarily required.

[0080] The method for modifying a conjugated diene polymer with a monomer having a carboxyl group is not particularly limited, but for example, a method of graft polymerizing a monomer having a carboxyl group to a conjugated diene polymer in an aqueous phase can be mentioned. The method for graft polymerizing a monomer having a carboxyl group in an aqueous phase is not particularly limited, and a conventionally known method may be used, but for example, a method of adding a monomer having a carboxyl group and a graft polymerization catalyst to a latex of a conjugated diene polymer, and then reacting the monomer having a carboxyl group with the conjugated diene polymer in an aqueous phase is preferred.

[0081] The graft polymerization catalyst is not particularly limited, but examples thereof include inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as diisopropylbenzene hydroperoxide, cumene hydroperoxide, t-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, di-t-butyl peroxide, isobutyryl peroxide, and benzoyl peroxide; and azo compounds such as 2,2'-azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and methyl azobisisobutyrate; and the like. From the viewpoint of further improving the tensile strength of the dip-molded article obtained, organic peroxides are preferred, and 1,1,3,3-tetramethylbutyl hydroperoxide is particularly preferred. These graft polymerization catalysts may be used alone or in combination of two or more.

[0082] The above graft polymerization catalysts can be used alone or in combination of two or more kinds. The amount of the graft polymerization catalyst used varies depending on the type, but is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 5 parts by weight, based on 100 parts by weight of the conjugated diene polymer. The method of adding the graft polymerization catalyst is not particularly limited, and known methods of addition such as lump-sum addition, divided addition, and continuous addition can be used.

[0083] In addition, the organic peroxide can be used as a redox polymerization initiator in combination with a reducing agent. The reducing agent is not particularly limited, but examples thereof include compounds containing reduced metal ions such as ferrous sulfate and cuprous naphthenate; sulfinates such as sodium hydroxymethanesulfinate; and amine compounds such as dimethylaniline. These reducing agents may be used alone or in combination of two or more.

[0084] The amount of the reducing agent to be added is not particularly limited, but is preferably 0.01 to 1 part by weight per 1 part by weight of the organic peroxide.

[0085] The method of adding the organic peroxide and the reducing agent is not particularly limited, and known methods of addition such as lump-sum addition, divided addition, continuous addition, etc. can be used.

[0086] The reaction temperature when reacting the conjugated diene polymer with the monomer having a carboxyl group is not particularly limited, but is preferably 15 to 80° C., more preferably 30 to 50° C. The reaction time when reacting the conjugated diene polymer with the monomer having a carboxyl group may be appropriately set depending on the reaction temperature, but is preferably 30 to 300 minutes, more preferably 60 to 120 minutes.

[0087] When the conjugated diene polymer is reacted with a monomer having a carboxyl group, the solid content concentration of the latex of the conjugated diene polymer is not particularly limited, but is preferably 5 to 60% by weight, more preferably 10 to 40% by weight.

[0088] Examples of monomers having a carboxyl group include ethylenically unsaturated monocarboxylic acid monomers such as acrylic acid and methacrylic acid; ethylenically unsaturated polycarboxylic acid monomers such as itaconic acid, maleic acid, fumaric acid, and butene tricarboxylic acid; partial ester monomers of ethylenically unsaturated polycarboxylic acids such as monobutyl fumarate, monobutyl maleate, and mono 2-hydroxypropyl maleate; and polycarboxylic anhydrides such as maleic anhydride and citraconic anhydride. Since the effects of the present invention are more pronounced, ethylenically unsaturated monocarboxylic acid monomers are preferred, acrylic acid and methacrylic acid are more preferred, and methacrylic acid is particularly preferred. These monomers may be used alone or in combination of two or more. The carboxyl group also includes salts with alkali metals, ammonia, and the like.

[0089] The amount of the monomer having a carboxyl group used is preferably 0.01 to 100 parts by weight, more preferably 0.01 to 40 parts by weight, even more preferably 0.5 to 20 parts by weight, and even more preferably 2 to 5 parts by weight, based on 100 parts by weight of the conjugated diene polymer. By setting the amount of the monomer having a carboxyl group used within the above range, the viscosity of the obtained latex composition becomes more appropriate, which makes it easier to transfer, and the tear strength of the dip-molded article formed using the obtained latex composition is further improved.

[0090] The method of adding the monomer having a carboxyl group to the latex of the conjugated diene polymer is not particularly limited, and any known addition method such as lump-sum addition, divided addition, continuous addition, etc. can be used.

[0091] The modification rate of the carboxy-modified conjugated diene polymer with a monomer having a carboxyl group may be appropriately controlled depending on the intended use of the resulting conjugated diene polymer latex composition, but is preferably 0.01 to 10% by weight, more preferably 0.2 to 5% by weight, even more preferably 0.3 to 3% by weight, particularly preferably 0.4 to 2% by weight, for example 0.4 to 1% by weight. The modification rate is represented by the following formula. Modification rate (wt%) = (X / Y) x 100 In the above formula, X represents the weight of the monomer unit having a carboxyl group in the carboxy-modified conjugated diene polymer, and Y represents the weight of the carboxy-modified conjugated diene polymer. 1 H-NMR measurement was performed. 1 It can be determined by a method of calculation from the results of H-NMR measurement, or a method of determining the amount of acid by neutralization titration and then calculating from the determined amount of acid.

[0092] The latex of the carboxy-modified conjugated diene polymer used in the present invention may contain additives that are usually added in the field of latexes, such as a pH adjuster, an antifoaming agent, a preservative, a chelating agent, an oxygen scavenger, a dispersant, and an antiaging agent.

[0093] Examples of pH adjusters include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal bicarbonates such as sodium bicarbonate; ammonia; and organic amine compounds such as trimethylamine and triethanolamine; with alkali metal hydroxides or ammonia being preferred.

[0094] The latex of the carboxy-modified conjugated diene polymer used in the present invention has a volume average particle diameter of 500 to 2,000 nm, preferably 650 to 1,500 nm, and more preferably 800 to 1,200 nm, of the particles of the carboxy-modified conjugated diene polymer dispersed in water. By setting the volume average particle diameter of the particles of the carboxy-modified conjugated diene polymer within the above range, the obtained dip-molded body can be excellent in tensile strength, tensile elongation, and tear strength, and the occurrence of structural defects such as pinholes can be suppressed, even if the thickness is as thin as 0.02 to 0.19 mm. If the volume average particle diameter of the particles of the carboxy-modified conjugated diene polymer is too small, the obtained dip-molded body will have poor tensile strength and tear strength, while if it is too large, aggregates will occur during the aging of the latex composition. The volume average particle diameter can be measured, for example, by a light scattering diffraction particle measuring device or a laser diffraction particle size distribution measuring device.

[0095] The latex composition used in the present invention preferably contains a sulfur-based vulcanizing agent in addition to the above-mentioned latex of the carboxy-modified conjugated diene polymer.

[0096] The sulfur-based vulcanizing agent is not particularly limited, but examples thereof include powdered sulfur, sulfur flowers, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, and other sulfur; sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, caprolactam disulfide (N,N'-dithio-bis(hexahydro-2H-azepinone-2)), phosphorus-containing polysulfide, polymer polysulfide, and sulfur-containing compounds such as 2-(4'-morpholinodithio)benzothiazole. Among these, sulfur is preferably used. The sulfur-based vulcanizing agent can be used alone or in combination of two or more.

[0097] The amount of the sulfur-based vulcanizing agent used is not particularly limited, but is preferably 0.01 to 3 parts by weight, more preferably 0.1 to 1.5 parts by weight, even more preferably 0.1 to 0.8 parts by weight, even more preferably 0.1 to 0.6 parts by weight, and particularly preferably 0.2 to 0.6 parts by weight, relative to 100 parts by weight of the carboxy-modified conjugated diene polymer contained in the latex composition. By setting the content of the sulfur-based vulcanizing agent within the above range, the tensile strength of the obtained dip-molded article can be further increased while suppressing the occurrence of delayed-type allergy (Type IV) symptoms.

[0098] The latex composition used in the present invention preferably contains a vulcanization accelerator in addition to the above-mentioned carboxy-modified conjugated diene polymer latex and sulfur-based vulcanizing agent. As the vulcanization accelerator, a xanthogen compound is preferably used from the viewpoint of suitably suppressing the occurrence of delayed-type allergy (Type IV) symptoms in the obtained dip-molded product.

[0099] Examples of xanthogen compounds include, but are not limited to, xanthogenic acid, xanthogen salts, xanthogen disulfides (compounds in which two xanthogenic acids are bonded via a sulfur atom or the like), and xanthogen polysulfides (compounds in which three or more xanthogenic acids are bonded via a sulfur atom or the like).

[0100] The xanthogenate may be any salt having a xanthogenic acid structure, and is not particularly limited thereto. For example, the xanthogenate may be a compound represented by the general formula (ROC(=S)S)xZ (wherein R is a linear or branched hydrocarbon, Z is a metal atom, and x is a number matching the valence of Z, and is usually 1 to 4, preferably 2 to 4, and particularly preferably 2).

[0101] The xanthogenate represented by the above general formula (ROC(=S)S)xZ is not particularly limited, and examples thereof include zinc dimethylxanthogenate, zinc diethylxanthogenate, zinc dipropylxanthogenate, zinc diisopropylxanthogenate, zinc dibutylxanthogenate, zinc dipentylxanthogenate, zinc dihexylxanthogenate, zinc diheptylxanthogenate, zinc dioctylxanthogenate, zinc di(2-ethylhexyl)xanthogenate, zinc didecylxanthogenate, zinc didodecylxanthogenate, potassium dimethylxanthogenate, potassium ethylxanthogenate, potassium propylxanthogenate, potassium isopropylxanthogenate, potassium butylxanthogenate, and potassium pentylxanthogenate. Examples of suitable xanthates include potassium xanthate, potassium hexyl xanthate, potassium heptyl xanthate, potassium octyl xanthate, potassium 2-ethylhexyl xanthate, potassium decyl xanthate, potassium dodecyl xanthate, sodium methyl xanthate, sodium ethyl xanthate, sodium propyl xanthate, sodium isopropyl xanthate, sodium butyl xanthate, sodium pentyl xanthate, sodium hexyl xanthate, sodium heptyl xanthate, sodium octyl xanthate, sodium 2-ethylhexyl xanthate, sodium decyl xanthate, and sodium dodecyl xanthogenate. Among these, xanthogenates in which x in the above general formula (ROC(=S)S)xZ is 2 or more are preferred, isopropyl xanthogenates and butyl xanthogenates are more preferred, and zinc diisopropyl xanthogenate and zinc dibutyl xanthogenate are particularly preferred. These xanthogenates may be used alone or in combination.

[0102] Xanthogen disulfide is a compound in which two xanthogenic acids are bonded via a sulfur atom or the like, and examples of such compounds include, but are not limited to, dimethylxanthogen disulfide, diethylxanthogen disulfide, diisopropylxanthogen disulfide, dibutylxanthogen disulfide, dimethylxanthogen polysulfide, diethylxanthogen polysulfide, diisopropylxanthogen polysulfide, and dibutylxanthogen polysulfide. Of these, diisopropylxanthogen disulfide and dibutylxanthogen disulfide are preferred.

[0103] Xanthogen polysulfides are compounds in which three or more xanthogenic acids are bonded together via sulfur atoms, etc., and examples include xanthogen trisulfide, in which three xanthogenic acids are bonded together via sulfur, xanthogen tetrasulfide, in which four xanthogenic acids are bonded together via sulfur, and xanthogen pentasulfide, in which five xanthogenic acids are bonded together via sulfur.

[0104] The latex composition may contain one kind of xanthogen compound alone, but preferably contains two or more kinds of xanthogen compounds. For example, when xanthogen acid is blended into the latex composition, a part of the blended xanthogen acid may exist in the form of a xanthogen salt, so that the latex composition contains two or more kinds of xanthogen compounds. Alternatively, a part of the xanthogen acid blended into the latex composition may exist in the form of a xanthogen disulfide or a xanthogen polysulfide due to the action of a sulfur-based vulcanizing agent in the latex composition. Similarly, when a xanthogen salt, a xanthogen disulfide, or a xanthogen polysulfide is blended into the latex composition, each of them may exist in the form of a xanthogen acid, a xanthogen salt, a xanthogen disulfide, or a xanthogen polysulfide.

[0105] In the present invention, a vulcanization accelerator other than the xanthogen compound may be used in place of the xanthogen compound or in addition to the xanthogen compound.

[0106] As the vulcanization accelerator other than such xanthogen compounds, those usually used in dip molding can be used, for example, dithiocarbamic acids such as diethyldithiocarbamic acid, dibutyldithiocarbamic acid, di-2-ethylhexyldithiocarbamic acid, dicyclohexyldithiocarbamic acid, diphenyldithiocarbamic acid, dibenzyldithiocarbamic acid, and zinc salts thereof; 2-mercaptobenzothiazole, 2-mercaptobenzothiazole zinc salt; Examples of the vulcanization accelerator include lead, 2-mercaptothiazoline, dibenzothiazyl disulfide, 2-(2,4-dinitrophenylthio)benzothiazole, 2-(N,N-diethylthio carbylthio)benzothiazole, 2-(2,6-dimethyl-4-morpholinothio)benzothiazole, 2-(4'-morpholino dithio)benzothiazole, 4-morpholinyl-2-benzothiazyl disulfide, and 1,3-bis(2-benzothiazyl mercaptomethyl)urea. The vulcanization accelerator can be used alone or in combination of two or more.

[0107] The amount of the vulcanization accelerator used (when multiple vulcanization accelerators are used, the total amount used) is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 7 parts by weight, even more preferably 0.5 to 5 parts by weight, and even more preferably 1 to 3 parts by weight, based on 100 parts by weight of the carboxy-modified conjugated diene polymer contained in the latex. By setting the amount of the vulcanization accelerator used within the above range, the tensile strength of the obtained dip-molded article can be further improved while suppressing an increase in hardness.

[0108] In addition, when the latex composition used in the present invention contains a xanthogen compound as a vulcanization accelerator, an activator may be added to the above-mentioned latex of the carboxy-modified conjugated diene polymer, if necessary.

[0109] By adding an activator to the latex composition, when the carboxy-modified conjugated diene polymer in the latex composition is vulcanized with a sulfur-based vulcanizing agent to form a dip-molded article using the latex composition, the activator acts as a vulcanization accelerator together with the xanthogen compound described above, thereby further improving the tear strength of the resulting dip-molded article.

[0110] The activator is not particularly limited, but it is preferable to use a metal compound from the viewpoint of further improving the tear strength of the dip-molded product obtained. The metal compound is not particularly limited, but for example, a metal oxide, a metal compound containing at least one carbon atom, etc. are mentioned. The metal constituting the metal compound is not particularly limited, but a typical metal (at least one element selected from the group consisting of Group 1 elements, Group 2 elements, Group 12 elements, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, Group 17 elements, and Group 18 elements) is preferable, Group 2 elements, Group 12 elements, Group 13 elements, and Group 14 elements are more preferable, zinc, magnesium, calcium, aluminum, and lead are further preferable, zinc, magnesium, and calcium are particularly preferable, and zinc is most preferable. These metal compounds may be used alone or in combination.

[0111] The metal oxide is not particularly limited, but from the viewpoint of further improving the tear strength of the obtained dip-molded body, zinc oxide, magnesium oxide, titanium oxide, calcium oxide, lead oxide, iron oxide, copper oxide, tin oxide, nickel oxide, chromium oxide, cobalt oxide, and aluminum oxide are preferred, and zinc oxide is more preferred.

[0112] As the metal compound containing at least one carbon atom, from the viewpoint of further improving the tear strength of the obtained dip-formed article, carbonates, hydrogencarbonates, hydroxides, and organometallic compounds are preferred, and carbonates, hydrogencarbonates, and organometallic compounds are more preferred. Among these, inorganic salts such as carbonates and hydrogencarbonates are particularly preferred from the viewpoint of excellent stability of the compound itself and easy availability.

[0113] The amount of the activator used is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and even more preferably 1 to 3 parts by weight, based on 100 parts by weight of the carboxy-modified conjugated diene polymer contained in the latex composition. By setting the amount of the activator used within the above range, the tear strength of the obtained dip-molded article can be further improved.

[0114] The method of blending the activator is not particularly limited as long as it is a method that ultimately results in a mixture of the carboxy-modified conjugated diene polymer latex and the activator.

[0115] Furthermore, the latex composition may further contain additives such as antioxidants; dispersants; reinforcing agents such as carbon black, silica, and talc; fillers such as calcium carbonate and clay; ultraviolet absorbers; and plasticizers, as required.

[0116] Antioxidants include 2,6-di-4-methylphenol, 2,6-di-t-butylphenol, butyl hydroxyanisole, 2,6-di-t-butyl-α-dimethylamino-p-cresol, octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, styrenated phenol, 2,2'-methylene-bis(6-α-methyl-benzyl-p-cresol), 4,4'-methylenebis(2,6-di-t-butylphenyl)propionate, butyl hydroxyanisole ... phenol-based antioxidants that do not contain sulfur atoms, such as 2,2'-methylene-bis(4-methyl-6-t-butylphenol), alkylated bisphenols, and butylated products of p-cresol and dicyclopentadiene; 2,2'-thiobis-(4-methyl-6-t-butylphenol), 4,4'-thiobis-(6-t-butyl-o-cresol), 2,6-di-t-butyl-4-(4,6-bis(octylthio)-1,3,5-trimethyl-2-phenylpropanediol), 2,2'-methylene-bis(4-methyl-6-t-butylphenol), alkylated bisphenols, and butylated products of p-cresol and dicyclopentadiene; Thiobisphenol-based antioxidants such as (triazin-2-ylamino)phenol; phosphite ester-based antioxidants such as tris(nonylphenyl)phosphite, diphenylisodecylphosphite, and tetraphenyldipropylene glycol diphosphite; sulfur ester-based antioxidants such as dilauryl thiodipropionate; phenyl-α-naphthylamine, phenyl-β-naphthylamine, p-(p-toluenesulfonylamido)-diphenyla amine-based antioxidants such as amine, 4,4'-(α,α-dimethylbenzyl)diphenylamine, N,N-diphenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, butyraldehyde-aniline condensate, quinoline-based antioxidants such as 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline, hydroquinone-based antioxidants such as 2,5-di-(t-amyl)hydroquinone, etc. These antioxidants can be used alone or in combination of two or more.

[0117] The content of the antioxidant is preferably 0.05 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and further preferably 1 to 3 parts by weight, based on 100 parts by weight of the carboxy-modified conjugated diene polymer.

[0118] The method of mixing various compounding agents into the latex composition is not particularly limited, but for example, a method of obtaining a composition containing a latex of a carboxy-modified conjugated diene polymer, a sulfur-based vulcanizing agent, and a vulcanization accelerator, and then mixing the obtained composition with various compounding agents to be mixed as necessary using a dispersing machine such as a ball mill, a kneader, or a disperser, etc. Also, at least a part of the various compounding agents may be mixed after aging, which will be described later.

[0119] The solid content of the latex composition used in the present invention is preferably 1 to 40% by weight, more preferably 3 to 35% by weight, further preferably 5 to 30% by weight, and particularly preferably 10 to 20% by weight. By setting the solid content of the latex composition within the above range, the aggregation stability of the latex in the obtained latex composition can be maintained at a high level, and the obtained dip-molded article can have excellent tensile strength, tensile elongation, and tear strength even when the thickness is as thin as 0.02 to 0.19 mm.

[0120] In the present invention, from the viewpoint of ensuring sufficient mechanical properties of the dip-molded article obtained, it is preferable to perform aging (precrosslinking or prevulcanization) of the above-mentioned latex composition before subjecting it to dip molding. The aging (prevulcanization) time is not particularly limited, but is preferably 8 to 120 hours, more preferably 24 to 72 hours. The aging (prevulcanization) temperature is not particularly limited, but is preferably 20 to 40°C. In addition, when using the above-mentioned latex composition, after performing aging (prevulcanization) for a predetermined time, dip molding may be continuously performed while maintaining the aging (prevulcanization) conditions (while continuing aging (prevulcanization)), and in this case, the aging (prevulcanization) time and aging (prevulcanization) temperature may be in the above-mentioned range.

[0121] <Method for producing dip-molded body> The method for producing the dip-molded article of the present invention includes the steps of: A step of immersing a dip-forming mold in a coagulant solution to adhere the coagulant to the dip-forming mold; providing a latex composition as described above; and immersing the dip-molding mold to which the coagulant has been attached in the latex composition to obtain a dip-molded product having a thickness of 0.02 to 0.19 mm.

[0122] According to the method for producing a dip-molded article of the present invention, a latex of a carboxy-modified conjugated diene polymer having a volume average particle size controlled in the range of 500 to 2,000 nm is used as the latex constituting the latex composition, and the thickness of the dip-molded article is controlled in the range of 0.02 to 0.19 mm. Even if the thickness is relatively thin, the obtained dip-molded article has excellent tensile strength, tensile elongation, and tear strength, and is suppressed in occurrence of structural defects such as pinholes.

[0123] The thickness of the dip-molded article obtained by the manufacturing method of the present invention is 0.02 to 0.19 mm, preferably 0.02 to 0.15 mm, more preferably 0.02 to 0.10 mm, and particularly preferably 0.02 mm or more and less than 0.08 mm. According to the manufacturing method of the present invention, when a latex of a carboxy-modified conjugated diene polymer in which the volume average particle diameter is controlled in the range of 500 to 2,000 nm is used, even if the thickness of the dip-molded article is within the above range, the tensile strength, tensile elongation, and tear strength of the dip-molded article obtained can be excellent. The thickness of the dip-molded article can be calculated, for example, as follows. That is, first, when the dip-molded mold described later is immersed in a coagulant solution, any five points within 3 cm from the part of the dip-molded article (usually the tip part of the dip-molded mold) corresponding to the part of the dip-molded mold that has the longest contact time with the coagulant solution are selected. Then, the thickness of the selected five points is measured, and the arithmetic average of the thicknesses of the five measured points is calculated, whereby the thickness can be calculated.

[0124] The dip molding die used in the present invention is not particularly limited, and various types of die can be used, such as die made of porcelain, glass, metal, plastic, etc. The shape of the dip molding die may be a desired shape according to the shape of the final product.

[0125] In addition, from the viewpoint of being able to suitably control the thickness of the obtained dip-molded article in the range of 0.02 to 0.19 mm, it is preferable to use a dip-molding mold whose surface has not been roughened (for example, ground). That is, it is preferable to use a dip-molding mold whose surface is smooth, and the surface roughness Ra of the dip-molding mold is preferably 0.01 to 100 μm, more preferably 0.1 to 50 μm, even more preferably 0.5 to 30 μm, and even more preferably 1 to 5 μm. Note that the surface roughness of a roughened glass mold is usually about several hundred to several thousand μm.

[0126] Specific examples of the coagulant include water-soluble polyvalent metal salts such as metal halides, such as barium chloride, calcium chloride, magnesium chloride, zinc chloride, and aluminum chloride; nitrates, such as barium nitrate, calcium nitrate, and zinc nitrate; acetates, such as barium acetate, calcium acetate, and zinc acetate; and sulfates, such as calcium sulfate, magnesium sulfate, and aluminum sulfate. Among these, calcium salts are preferred, and calcium nitrate is more preferred. These water-soluble polyvalent metal salts can be used alone or in combination of two or more.

[0127] The coagulant is usually used as a solution of water, alcohol, or a mixture thereof, and is preferably used in the form of an aqueous solution. This aqueous solution may further contain a water-soluble organic solvent such as methanol or ethanol, or a nonionic surfactant. The concentration of the coagulant varies depending on the type of water-soluble polyvalent metal salt, but is preferably 0.1 to 20% by weight, more preferably 0.2 to 15% by weight, even more preferably 0.3 to 10% by weight, particularly preferably 0.5 to 6% by weight, for example 1 to 4% by weight. By setting the coagulant concentration within the above range, the thickness of the obtained dip-molded body can be suitably controlled.

[0128] The immersion time when the dip-forming mold is immersed in the coagulant solution is preferably 0.1 to 20 seconds, more preferably 0.5 to 10 seconds, further preferably 1 to 6 seconds, and particularly preferably 1 to 4 seconds. By setting the immersion time when immersing in the coagulant solution within the above range, the thickness of the obtained dip-formed body can be suitably controlled.

[0129] It is preferable to heat the dip molding mold when immersing it in the coagulant solution, and the temperature of the dip molding mold at this time is preferably 20 to 100° C., more preferably 30 to 80° C., further preferably 35 to 70° C., and particularly preferably 40 to 65° C. By controlling the temperature of the dip molding mold within the above range, the thickness of the obtained dip molded article can be suitably controlled.

[0130] The immersion time when the dip molding mold to which the coagulant is attached is immersed in the latex composition is preferably 1 to 20 seconds, more preferably 1 to 15 seconds, further preferably 2 to 10 seconds, and particularly preferably 3 to 6 seconds. By setting the immersion time when immersing in the latex composition within the above range, the thickness of the obtained dip molded article can be suitably controlled.

[0131] After the dip-molding mold is removed from the latex composition, the deposit formed on the dip-molding mold is usually dried by heating under appropriately selected drying conditions.

[0132] Next, the dip-molded layer formed on the dip-molding mold is crosslinked by heating. The dip-molded layer can be crosslinked by heating at a temperature of 80 to 150°C for preferably 10 to 130 minutes. The heating method can be external heating using infrared rays or heated air, or internal heating using high frequency waves. Of these, external heating using heated air is preferred. Before the heat treatment, the dip-molded layer may be immersed in water, preferably in warm water at 30 to 70°C, for about 1 to 60 minutes to remove water-soluble impurities (for example, excess emulsifier, coagulant, etc.). The operation of removing water-soluble impurities may be performed after the dip-molded layer is heat-treated, but it is preferable to perform the operation before the heat treatment in order to more efficiently remove water-soluble impurities.

[0133] The dip-molded layer is then removed from the dip mold to obtain a dip-molded body. The method for removing the dip-molded layer may be a method of peeling the layer from the dip mold by hand or by using water pressure or compressed air. After the removal, the layer may be further heated at a temperature of 60 to 120°C for 10 to 120 minutes.

[0134] In this manner, in the production method of the present invention, as described above, the latex constituting the latex composition is a latex of a carboxy-modified conjugated diene polymer having a volume average particle size controlled in the range of 500 to 2,000 nm, and the thickness of the dip-molded article is controlled in the range of 0.02 to 0.19 mm. Even if the thickness is made relatively thin, the obtained dip-molded article has excellent tensile strength, tensile elongation, and tear strength, and the occurrence of structural defects such as pinholes is suppressed. Therefore, the obtained dip-molded article can be particularly suitably used as, for example, a probe cover, a condom, or a surgical glove.

[0135] In addition to the above, the dip-molded articles obtained by the manufacturing method of the present invention can also be used for medical products such as baby bottle nipples, droppers, tubes, water pillows, balloon sacks, and catheters; toys such as balloons, dolls, and balls; industrial products such as pressure molding bags and gas storage bags; and finger cots. EXAMPLES

[0136] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In addition, the "parts" below are based on weight unless otherwise specified. In addition, various physical properties were measured as follows.

[0137] <Solid content concentration> 2 g of the sample was weighed out (weight: X2) onto an aluminum dish (weight: X1), and dried for 2 hours in a hot air dryer at 105° C. Then, after cooling in a desiccator, the weight of the aluminum dish was measured (weight: X3), and the solid content was calculated according to the following formula. Solid content concentration (wt%)=(X3-X1)×100 / X2

[0138] <Modification ratio of carboxy-modified conjugated diene polymer> The number of carboxyl groups in the carboxyl-modified conjugated diene polymer (carboxyl-modified synthetic polyisoprene and carboxyl-modified SIS) constituting the latex of the carboxyl-modified conjugated diene polymer (carboxyl-modified synthetic polyisoprene latex and carboxyl-modified SIS latex) was determined by neutralization titration using an aqueous sodium hydroxide solution. Next, based on the number of carboxyl groups determined, the modification rate by the monomer having a carboxyl group was determined according to the following formula. Modification rate (wt%) = (X / Y) x 100 In the above formula, X represents the weight of the monomer unit having a carboxyl group in the carboxy-modified conjugated diene polymer, and Y represents the weight of the carboxy-modified conjugated diene polymer.

[0139] <Volume average particle size of carboxy-modified conjugated diene polymer particles> The volume average particle size of the carboxy-modified conjugated diene polymer particles contained in the carboxy-modified conjugated diene polymer latex was measured using a light scattering diffraction particle analyzer (product name "LS-230", manufactured by Coulter).

[0140] <Thickness of dip-molded product> When the glass mold was immersed in the coagulant solution, five measurement points were selected within 3 cm from the part of the dip-molded body that corresponds to the part (the tip of the glass mold) that had the longest contact time with the coagulant solution. The thicknesses of the five selected points were then measured, and the arithmetic mean of the five thicknesses measured was calculated. The obtained value (unit: mm) was regarded as the thickness of the dip-molded body.

[0141] <500% tensile stress, tensile strength, and tensile elongation of dip-molded body> Based on ASTM D412, the dip-molded body was punched out with a dumbbell (product name "Super Dumbbell (model: SDMK-100C)" manufactured by Dumbbell Co., Ltd.) to prepare a test piece for measuring tensile strength. The test piece was pulled at a tensile speed of 500 mm / min with a Tensilon universal testing machine (product name "RTG-1210" manufactured by Orientec Co., Ltd.), and the tensile stress (unit: MPa) at an elongation rate of 500%, the tensile strength (unit: MPa) just before break, and the tensile elongation (unit: %) just before break were measured. The lower the 500% tensile stress value, the softer the dip-molded body is judged to be. Also, the higher the tensile strength, the better the mechanical strength of the dip-molded body is judged to be.

[0142] <Tear strength of dip-molded body> Based on ASTM D624-00, the dip-molded body was left in a constant temperature and humidity room at 23°C and 50% relative humidity for 24 hours or more, and then punched out with a dumbbell (product name "Die C", manufactured by Dumbbell Co., Ltd.) to prepare a test piece for measuring tear strength. The test piece was pulled at a tensile speed of 500 mm / min with a Tensilon universal testing machine (product name "RTG-1210", manufactured by A&D Co., Ltd.) to measure tear strength (unit: N / mm). It can be determined that the higher the tear strength, the better the mechanical strength of the dip-molded body.

[0143] <Number of pinholes in dip-molded product> The number of pinholes in the dip-molded product was measured by cutting one dip-molded product with scissors into a sheet, irradiating the back side of the cut-open sheet with a backlight while observing the surface of the sheet with a magnifying glass, and counting the number of pinholes. The number of pinholes per dip-molded product was recorded as the number of pinholes in the dip-molded product.

[0144] <Example 1> (Production of carboxy-modified synthetic polyisoprene (A-1) latex) Synthetic polyisoprene (product name "NIPOL IR2200L", manufactured by Zeon Corporation) was mixed with n-hexane (boiling point: 69°C) and dissolved by heating to 60°C with stirring to prepare an n-hexane solution of synthetic polyisoprene (a) with a synthetic polyisoprene concentration of 15% by weight.

[0145] On the other hand, potassium rosinate was added to water and dissolved by raising the temperature to 60° C. to prepare an aqueous emulsifier solution (b) with a concentration of 1.5% by weight.

[0146] Next, the synthetic polyisoprene n-hexane solution (a) obtained above and the emulsifier aqueous solution (b) were mixed using a mixer (product name "Multi Line Mixer MS26-MMR-5.5L", manufactured by Satake Chemical Machinery Co., Ltd.) so that the potassium rosinate in the emulsifier aqueous solution (b) was 10 parts per 100 parts of synthetic polyisoprene in the synthetic polyisoprene n-hexane solution (a), and then mixed and emulsified at a rotation speed of 4100 rpm using an emulsifier (product name "Milder MDN310", manufactured by Pacific Machinery Co., Ltd.) to obtain an emulsified dispersion (c). At this time, the total feed flow rate of the synthetic polyisoprene n-hexane solution (a) and the emulsifier aqueous solution (b) was 2,000 kg / hr, the temperature was 60°C, and the back pressure (gauge pressure) was 0.5 MPa.

[0147] Next, the obtained emulsion dispersion (c) was heated to 80°C under reduced pressure of -0.01 to -0.09 MPa (gauge pressure) to distill off n-hexane, and an aqueous dispersion of synthetic polyisoprene (d) was obtained. At this time, an antifoaming agent (product name "SM5515", manufactured by Dow Corning Toray Co., Ltd.) was continuously added while spraying so that the amount was 300 ppm by weight relative to the synthetic polyisoprene in the emulsion dispersion (c). When distilling off n-hexane, the emulsion dispersion (c) was adjusted to 70% by volume or less of the tank volume, and stirring was performed slowly at 60 rpm using a three-stage inclined paddle impeller as the stirring impeller.

[0148] After completion of distillation of n-hexane, the obtained aqueous dispersion of synthetic polyisoprene (d) was concentrated by centrifuging at 8,000 to 9,000 G using a continuous centrifuge (product name "SRG510", manufactured by Alfa Laval) to obtain a synthetic polyisoprene latex (e) having a solid content concentration of 60% by weight as a light liquid. The conditions of the centrifugation were as follows: the aqueous dispersion (d) before centrifugation had a solid content concentration of 8% by weight, the flow rate during continuous centrifugation was 1300 kg / hr, and the back pressure (gauge pressure) of the centrifuge was 0.1 MPa.

[0149] Next, 130 parts of distilled water was added to 100 parts of synthetic polyisoprene in the obtained synthetic polyisoprene latex (e) to dilute it. Then, 0.8 parts of sodium salt of β-naphthalenesulfonic acid formalin condensate (trade name "Demol T-45", manufactured by Kao Corporation) as a dispersant was diluted with 4 parts of distilled water per 100 parts of synthetic polyisoprene to the synthetic polyisoprene latex (e) over 5 minutes. Next, the synthetic polyisoprene latex (e) to which the dispersant was added was charged in a nitrogen-substituted reaction vessel equipped with a stirrer, and the temperature was heated to 30°C while stirring. In addition, a methacrylic acid dilution solution was prepared by mixing 3 parts of methacrylic acid as a carboxyl group-containing compound and 16 parts of distilled water using another vessel. This methacrylic acid dilution solution was added to a reaction vessel kept at a temperature of 20°C over 30 minutes.

[0150] Furthermore, a solution (f) consisting of 7 parts of distilled water, 0.32 parts of sodium formaldehyde sulfoxylate (trade name "SFS", manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 0.01 parts of ferrous sulfate (trade name "Frost Fe", manufactured by Chubu Chelest Co., Ltd.) was prepared using another container. After transferring this solution (f) into a reaction container, 0.5 parts of 1,1,3,3-tetramethylbutyl hydroperoxide (trade name "Perocta H", manufactured by Nippon Oil & Fats Co., Ltd.) was added and reacted at 20°C for 1 hour, and then concentrated by a centrifuge to obtain a latex of carboxy-modified synthetic polyisoprene (A-1). The modification rate of the obtained latex of carboxy-modified synthetic polyisoprene (A-1) was measured according to the above method, and the modification rate was 0.5 mol%. In addition, the volume average particle diameter of the particles of carboxy-modified synthetic polyisoprene contained in the obtained latex of carboxy-modified synthetic polyisoprene (A-1) was 0.91 μm.

[0151] (Preparation of Latex Composition) While stirring the latex of the carboxy-modified synthetic polyisoprene (A-1) obtained above, 1.5 parts of sulfur, 2.5 parts of zinc diisopropylxanthate as a vulcanization accelerator, 1.5 parts of zinc oxide as an activator, and 2 parts of an antioxidant (trade name "Wingstay L", manufactured by Goodyear) were added in terms of solid content to 100 parts of the carboxy-modified synthetic polyisoprene (A-1) in the latex of the carboxy-modified synthetic polyisoprene (A-1), and water dispersions of each compounding agent were added to adjust the solid content concentration by adding water to obtain a latex composition. The obtained latex composition was then aged (pre-vulcanized) for 48 hours in a thermostatic water bath adjusted to 25°C to obtain a latex composition with a solid content concentration of 10% by weight.

[0152] (Production of dip-molded body) A glass mold (surface roughness Ra: 2 μm) was washed and preheated in an oven at 40° C., then immersed in an aqueous coagulant solution containing 3% by weight of calcium nitrate and 0.05% by weight of polyoxyethylene lauryl ether (product name "Emulgen 109P", Kao Corporation) for 3 seconds and removed from the aqueous coagulant solution. The glass mold was then dried in an oven at 70° C. for 30 minutes or more to adhere the coagulant to the glass mold, thereby coating the glass mold with the coagulant.

[0153] Then, the glass mold coated with the coagulant was removed from the oven and immersed in the latex composition obtained above for 6 seconds. Next, the glass mold was air-dried at room temperature for 10 minutes, and then immersed in 60°C warm water for 5 minutes to dissolve water-soluble impurities, forming a dip-molded layer on the glass mold. Then, the dip-molded layer formed on the glass mold was vulcanized by heating in an oven at a temperature of 130°C for 30 minutes, cooled to room temperature, and talc was sprayed on it, and then peeled off from the glass mold to obtain a dip-molded body. The thickness of the obtained dip-molded body was 0.03 mm. Then, using the obtained dip-molded body, 500% tensile stress, tensile strength, tensile elongation, tear strength, and number of pinholes were measured according to the above-mentioned method. The results are shown in Table 1.

[0154] <Example 2> A dip-formed body was produced and evaluated in the same manner as in Example 1, except that the immersion time when immersing the glass mold in the coagulant aqueous solution was changed to 10 seconds. The results are shown in Table 1. The thickness of the obtained dip-formed body was 0.05 mm.

[0155] <Example 3> A dip-molded article was produced and evaluated in the same manner as in Example 2, except that the immersion time when the glass mold coated with the coagulant was immersed in the latex composition was changed to 15 seconds. The results are shown in Table 1. The thickness of the obtained dip-molded article was 0.07 mm.

[0156] <Example 4> (Preparation of Latex Composition) A latex composition was obtained in the same manner as in Example 1, except that the solid content was changed to 20% by weight.

[0157] (Production of dip-molded body) A glass mold (surface roughness Ra: 2 μm) was washed and preheated in an oven at 60° C., then immersed in an aqueous coagulant solution containing 6% by weight of calcium nitrate and 0.05% by weight of polyoxyethylene lauryl ether (product name "Emulgen 109P", Kao Corporation) for 3 seconds and removed from the aqueous coagulant solution. The glass mold was then dried in an oven at 70° C. for 30 minutes or more to adhere the coagulant to the glass mold, thereby coating the glass mold with the coagulant.

[0158] Thereafter, the glass mold coated with the coagulant was removed from the oven and immersed in the latex composition obtained above for 6 seconds. Next, the glass mold was air-dried at room temperature for 10 minutes, and then immersed in warm water at 60°C for 5 minutes to dissolve water-soluble impurities, forming a dip-molded layer on the glass mold. Thereafter, the dip-molded layer formed on the glass mold was vulcanized by heating in an oven at a temperature of 130°C for 30 minutes, and then cooled to room temperature, talc was sprayed, and the layer was peeled off from the glass mold to obtain a dip-molded body. The thickness of the obtained dip-molded body was 0.09 mm. Then, the obtained dip-molded body was evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0159] <Example 5> A latex composition was obtained in the same manner as in Example 1, except that the solid content concentration was changed to 30% by weight. Then, using the obtained latex composition, a dip-molded article was produced in the same manner as in Example 4, except that the coagulant concentration was changed to 12% by weight, and was evaluated in the same manner. The results are shown in Table 1. The thickness of the obtained dip-molded article was 0.16 mm.

[0160] <Example 6> A latex composition having a solid content concentration of 10% by weight was obtained in the same manner as in Example 1, except that the amount of the aqueous sulfur dispersion was changed so that the amount of sulfur was 0.5 parts. Then, a dip-molded product was produced and evaluated in the same manner as in Example 1, except that the obtained latex composition was used. The results are shown in Table 1. The thickness of the obtained dip-molded product was 0.03 mm.

[0161] <Comparative Example 1> A dip-molded article was produced and evaluated in the same manner as in Example 2, except that the synthetic polyisoprene latex (e) was used instead of the carboxy-modified synthetic polyisoprene latex (A-1). The results are shown in Table 1. The thickness of the obtained dip-molded article was 0.09 mm.

[0162] <Comparative Example 2> A dip-molded article was produced and evaluated in the same manner as in Example 5, except that the synthetic polyisoprene latex (e) was used instead of the carboxy-modified synthetic polyisoprene latex (A-1). The results are shown in Table 1. The thickness of the obtained dip-molded article was 0.21 mm.

[0163] <Comparative Example 3> A dip-formed article was produced and evaluated in the same manner as in Example 5, except that the coagulant concentration was changed to 0.1% by weight. The results are shown in Table 1. The thickness of the obtained dip-formed article was 0.01 mm.

[0164] [Table 1]

[0165] <Example 7> (Production of carboxy-modified SIS (A-2) latex) A latex of carboxy-modified SIS (A-2) was obtained in the same manner as in Example 1, except that a styrene-isoprene-styrene block copolymer (SIS) (product name "Quintac 3620", manufactured by Zeon Corporation) was used instead of synthetic polyisoprene (product name "NIPOL IR2200L", manufactured by Zeon Corporation). The volume average particle diameter of the particles of carboxy-modified SIS (A-2) contained in the obtained latex of carboxy-modified SIS (A-2) was 0.64 μm.

[0166] A dip-molded article was produced and evaluated in the same manner as in Example 5, except that the latex of the carboxy-modified synthetic polyisoprene (A-1) was replaced with the latex of the carboxy-modified SIS (A-2). The results are shown in Table 2. The thickness of the obtained dip-molded article was 0.17 mm.

[0167] [Table 2]

[0168] A dip molding mold was immersed in a coagulant solution, and then immersed in a latex composition containing a carboxy-modified conjugated diene polymer latex in which particles of a carboxy-modified conjugated diene polymer having a volume average particle size of 500 to 2,000 nm are dispersed in water. The dip moldings obtained by this manufacturing method had a thickness of 0.02 to 0.19 mm and were free of pinholes, had good tensile stress, and were excellent in tensile strength, tensile elongation, and tear strength (Examples 1 to 7). On the other hand, when a latex composition containing a conjugated diene polymer latex including a non-carboxyl-modified conjugated diene polymer was used, many pinholes were observed in the obtained dip-molded body (Comparative Examples 1 and 2). Furthermore, when a dip-formed article having a thickness of less than 0.02 was produced, the resulting dip-formed article had low tensile strength and tear strength (Comparative Example 3).

Claims

1. A step of immersing a dip-forming mold in a coagulant solution to adhere the coagulant to the dip-forming mold; A step of preparing a latex composition containing a carboxy-modified conjugated diene polymer latex in which particles of a carboxy-modified conjugated diene polymer having a volume average particle diameter of 500 to 2,000 nm are dispersed in water; and a step of immersing the dip-molding mold to which the coagulant has been attached in the latex composition to obtain a dip-molded product having a thickness of 0.02 mm or more and less than 0.08 mm. the carboxy-modified conjugated diene polymer latex is a synthetic polyisoprene, a styrene-isoprene-styrene block copolymer, or a deproteinized natural rubber latex; The coagulant concentration of the coagulant solution is 1 to 4% by weight; The method for producing a dip-molded article, wherein the solid content concentration of the latex composition is 10 to 20% by weight.

2. The method for producing a dip-molded article according to claim 1 , wherein the dip-molding mold has a surface that has not been roughened.

3. 3. The method for producing a dip-formed article according to claim 1, wherein the dip-forming mold is immersed in the coagulant solution for a period of 0.1 to 20 seconds.

4. The method for producing a dip-molded article according to any one of claims 1 to 3, wherein the temperature of the dip-molding mold is set to 20 to 100°C when the dip-molding mold is immersed in the coagulant solution.

5. 5. The method for producing a dip-molded article according to claim 1, wherein the dip-molding mold having the coagulant attached thereto is immersed in the latex composition for a period of 1 to 20 seconds.

6. The method for producing a dip-molded article according to any one of claims 1 to 5, wherein the latex composition further contains a sulfur-based vulcanizing agent.

7. The method for producing a dip-molded article according to claim 6, wherein the latex composition further contains a vulcanization accelerator.

8. The method for producing a dip-molded article according to claim 7, wherein the vulcanization accelerator is a xanthogen compound.

Citation Information

Patent Citations

  • Latex for dip molding use, composition for dip molding use, and dip-molded article

    WO2014129547A1

  • Latex composition for dip molding and dip-molded article

    WO2016104057A1

  • Latex composition

    WO2018155243A1

  • Production method for latex composition

    WO2019058807A1